A retrospective cohort study comparing high and low balloon inflation pressure on technical success and patency for treating central venous lesions in patients on chronic hemodialysis. Issue 1 (1st January 2021) - Cui, Long; Gao, Dan; Lu, Xiaohan; Gao, Zhao; Yuan, Hai; Hu, Fengqi
Abstract: Background: We aimed to analyze the success rates and the access patency rates at 12 months between patients on chronic hemodialysis with symptomatic central venous stenosis (CVS) or occlusion (CVO), receiving high or low balloon inflation pressure for treatment. Methods: We performed a retrospective study in which angioplasty balloons were inflated using a low-pressure or a high-pressure for the management of hemodialysis patients with CVS/CVO. The outcomes of this study were the success rate and the access patency rates at 12 months after balloon angioplasty, and the differences between groups were compared. Results: We included a total of 74 patients on hemodialysis and assigned them to the low-pressure or the high-pressure groups. Success rates in patients of the high-pressure group (94.12%) were higher than those in patients of the low-pressure group (67.50%) ( p = 0.005). With a total of 59 patients with technical success, at 6 and 12 months after angioplasty, the rates of access patency in the low-pressure group were 68 and 48%, respectively; on the other hand, the primary patency rates in the high-pressure group were 86.67% (6-months) and 76.67% (12-months). The 6 and 12 months post-interventional patency rates were higher in patients of the high-pressure group than those in patients of the low-pressure group ( p = 0.10 at 6 months an d p = 0.03 at 12 months). Conclusions: Compared to balloon angioplasty using a low inflation pressure, hemodialysis patients with CVS/CVO receiving angioplasty using a high inflation pressure have significantly higher technical success and 12-month patency rates.